1977
DOI: 10.1037/0012-1649.13.3.225
|View full text |Cite
|
Sign up to set email alerts
|

Intrasensory and intersensory perception of temporal sequences during infancy.

Abstract: The purpose of the present study was to investigate sensory integration in infants. Two groups of infants were repeatedly presented with a standard visual or auditory temporal sequence in a habituation period. In the test period, each group was divided into four subgroups in which the presentation modality and/or the temporal sequence remained the same or were different. Subjects who were presented a different temporal sequence in the test period produced larger responses than did subjects who were presented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…Infants also detect amodal information specifying affective expression across the visual and acoustic stimulation of speech (Walker-Andrews, 1997) as well as information specifying the age and gender of a speaker (Bahrick, Netto, & Hernandez-Reif, 1998; Walker-Andrews, Bahrick, Raglioni, & Diaz, 1991). In perceiving moving objects, infants detect amodal temporal information specifying the substance and composition of an object across the sights and sounds of its impacts against a surface (Bahrick, 1983(Bahrick, , 1988(Bahrick, , 1992 as well as the common tempo of action and rhythm (Allen, Walker, Symonds, & Marcell, 1977;Lewkowicz, 2000;Spelke, 1979;Spelke, Born, & Chu, 1983). These experiments demonstrate that within the first 6 months of postnatal development, infants are skilled perceivers of amodal information uniting stimulation across sensory modalities.…”
mentioning
confidence: 98%
“…Infants also detect amodal information specifying affective expression across the visual and acoustic stimulation of speech (Walker-Andrews, 1997) as well as information specifying the age and gender of a speaker (Bahrick, Netto, & Hernandez-Reif, 1998; Walker-Andrews, Bahrick, Raglioni, & Diaz, 1991). In perceiving moving objects, infants detect amodal temporal information specifying the substance and composition of an object across the sights and sounds of its impacts against a surface (Bahrick, 1983(Bahrick, , 1988(Bahrick, , 1992 as well as the common tempo of action and rhythm (Allen, Walker, Symonds, & Marcell, 1977;Lewkowicz, 2000;Spelke, 1979;Spelke, Born, & Chu, 1983). These experiments demonstrate that within the first 6 months of postnatal development, infants are skilled perceivers of amodal information uniting stimulation across sensory modalities.…”
mentioning
confidence: 98%
“…Infants also appear to possess some of these abilities. For example, it has been reported that infants can detect auditory-visual equivalence on the basis of intensity (Lewkowicz & Turkewitz, 1980), rate (Spelke, 1979), rhythm (Allen, Walker, Symonds, & Marcell, 1977;Mendelson & Ferland, 1982), linguistic content (Kuhl & Meltzoff, 1982), and synchrony (Bahrick, 1987;Lewkowicz, in press) as early as 3-4 months of age, and on the basis of duration/synchrony by 6 months of age (Lewkowicz, 1986).…”
Section: New York State Institute For Basic Research In Developmentalmentioning
confidence: 99%
“…The perception of an invariant relationship between audio and visual stimulation emerges at very precocious ages. At 4-5 months infants are able to detect synchrony between visual and acoustic stimuli [40,41], to make associations between sounds and changes in the direction of a movement [42,43], to match faces and voices (e.g., [44,45]) and to recognize similarities between the common rhythmic structures, tempo, and duration of auditory and visual events ( [46][47][48]; see [49], for a review). Within this cross-modal context it is also well known that humans spontaneously describe auditory pitch spatially (e.g., [50][51][52]).…”
Section: Introductionmentioning
confidence: 99%